Cognitive-behavioural processes during route previewing in bouldering - Medernach, J. P.; Sanchez, X.; Henz, J.; Memmert, D. (Psychology of Sport and Exercise, 2024)
Introduction In the Olympic climbing discipline of bouldering, climbers can preview boulders before actually climbing them. Whilst such pre-climbing route previewing is considered as central to subsequent climbing performance, research on cognitive-behavioural processes during the preparatory phase in the modality of bouldering is lacking. The present study aimed at extending existing findings on neural efficiency processes associated with advanced skill level during motor activity preparation by examining cognitive-behavioural processes during the previewing of boulders.